Peningkatan Media Informasi Desa Melalui Website Di Dusun Air Gemuruh Kecamatan Bhatin III Kabupaten Bungo - Alam, Sandi; Zulkifli; Juniarsih, Delvita; Syahwami; Muhammad Nasir, H.; Ernawati (HIMPUNAN DOSEN GEMILANG INDONESIA, 2024)
Website or usually abbreviated as web is an information page provided via the internet so that it can be accessed worldwide as long as it is connected to the internet network. A website is a collection of pages that display text data information, still image data or, animation data, sound, video and or a combination of all of them, both static and dynamic which form a series of interrelated buildings where each is connected to a network of pages. Currently the web is one of the effective media to be used as an information media because of its very wide coverage, namely the whole world. In making the Dusun Air Gemuruh website, we needed several weeks, for the web template we used the hamlet information system from OpenSid then after the hamlet website was ready, we conducted socialization to the Dusun Air Gemuruh apparatus regarding the use and maintenance of the Dusun Air Gemuruh website. With the existence of the Dusun Air Gemuruh website, it is hoped that it can become a new and useful information media for both the village and the Dusun community itself and the outside community.